2019
DOI: 10.1111/csp2.29
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing cat‐owner behaviors for a campaign to reduce wildlife depredation

Abstract: Behavior prioritization is underutilized but critical to the success of conservation campaigns. It provides an understanding of the target audience's values, transcending conflict, and informing the design of achievable and effective advocacy campaigns. Depredation by domestic cats may depress wildlife populations, leading to conflict between cat owners and conservationists. We surveyed veterinarians and cat owners at veterinary clinics to prioritize a list of nine cat‐management behaviors. Cat‐owner behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 64 publications
1
57
2
Order By: Relevance
“…Given that cat populations and behaviour are influenced, directly and indirectly, by human behaviour, integrating cat owners as research participants will be vital to improving our understanding of human-cat-environment relations, and to the development and application of effective, sustainable solutions to the environmental challenges created by the global abundance of people and their cats. Recent research has provided important insights into drivers of cat owner behaviour [28,[30][31][32] and the effectiveness of different techniques for communication and behaviour change [33][34][35]. However, beyond behaviour change initiatives, good-faith engagement between cat owners and advocates, wildlife conservationists, and scientists will be vital to understanding differing perspectives, concerns, and priorities, and to constructively deliberating on human responsibilities to and for domestic cats.…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…Given that cat populations and behaviour are influenced, directly and indirectly, by human behaviour, integrating cat owners as research participants will be vital to improving our understanding of human-cat-environment relations, and to the development and application of effective, sustainable solutions to the environmental challenges created by the global abundance of people and their cats. Recent research has provided important insights into drivers of cat owner behaviour [28,[30][31][32] and the effectiveness of different techniques for communication and behaviour change [33][34][35]. However, beyond behaviour change initiatives, good-faith engagement between cat owners and advocates, wildlife conservationists, and scientists will be vital to understanding differing perspectives, concerns, and priorities, and to constructively deliberating on human responsibilities to and for domestic cats.…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…However, other research indicates that many owners are less willing to confine their cats to protect wildlife (e.g., [77][78][79]). A survey from New Zealand, targeted to veterinarians and cat owners to prioritize cat management behaviors, revealed that bringing cats in at night was likely to be adopted by cat owners, but confining cats inside 24-h per day was not supported by veterinarians and was unlikely to be adopted by cat owners [80]. Clancy and colleagues [15] surveyed 184 cat owners in Massachusetts in the United States on which factors influence owner provision of outdoor access for cats.…”
Section: Human Attitudes About Provision Of Outdoor Access For Catsmentioning
confidence: 99%
“…Prioritizing behaviors begins by identifying and defining those behaviors likely to have the greatest positive or negative impact on biodiversity (Clayton, Litchfield, & Geller, 2013;Schultz, 2011), a process determined in part by the objectives or scale of the behavior change program. For instance, previous conservation research has prioritized the most impactful cat-owner behaviors (e.g., cat containment and cat collaring) in New Zealand (Linklater et al, 2019), and individual behaviors to reduce the impact of wild dogs (e.g., trapping wild dogs and abstain from feeding wild dogs) in peri-urban communities of Australia (Please et al, 2018). These studies selected a subset of behaviors that addressed a specific conservation problem (e.g., cat predation of native animals) among a specific audience (e.g., cat owners in New Zealand).…”
Section: Identifying Biodiversity Behaviorsmentioning
confidence: 99%
“…They are therefore harder to measure and contain a higher degree of uncertainty (Butchart et al, 2010;Scholes & Biggs, 2005). To overcome the problem of a lack of a standard unit of measurement, Please et al (2018) and Linklater et al (2019) used expert estimates (measured by numerical scales) to determine the effectiveness of changing specific behaviors on targeted outcomes that benefit biodiversity.…”
Section: Estimating Behavioral Impact Plasticity and Prevalencementioning
confidence: 99%
See 1 more Smart Citation